Blue Ocean Strategy to Increase the Competitiveness of Egy Shell Craft Exports - Desak Made Wulandewi; Luh Putu Mahyuni (Budapest International Research and Critics University, 2022)
In the face of intense competition, competitive strategy is very important in facing business competition. This study aims to explore how the Blue Ocean Strategy can be applied to the shellfish industry and other industries to increase export volume. The type of research used is qualitative research. Data collection through interviews. Determination of interview informants using purposive sampling technique. The validity of the data was tested using source triangulation. From the research results, the competitive strategy used by Egy Shell at this time is a focus and branding strategy. Egy Shell is becoming more focused on customer service and making the company more widely known. On the other hand, the company faces a tight competitive strategy because competitors are also targeting the same market. Improvements to the current competitive strategy are needed and it is necessary to formulate a new strategy using the Blue Ocean Strategy. From the formulation of the competitive strategy, new strategies that can be applied include: improving Product Quality by increasing the skill of craftsman, marketing by utilizing social media. In addition, it is necessary to create adequate supporting facilities, create a company website to make consumer easier get company’s information, maximize the timeliness of product completion and carry out product innovations on a regular basis to increase product value.